2020
DOI: 10.1002/ange.201913865
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Iron–Nickel Nanoparticles for Magnetically Induced CO2Methanation in Continuous Flow

Abstract: Induction heating of magnetic nanoparticles (NPs) is a method to activate heterogeneous catalytic reactions. It requires nano‐objects displaying high heating power and excellent catalytic activity. Here, using a surface engineering approach, bimetallic NPs are used for magnetically induced CO2 methanation, acting both as heating agent and catalyst. The organometallic synthesis of Fe30Ni70 NPs displaying high heating powers at low magnetic field amplitudes is described. The NPs are active but only slightly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Importantly, in situ infrared thermography was employed to examine the surface temperatures and development of hotspots due to the exothermicity of the reaction on structured catalysts based on different foams, showing that both SiC and aluminium foams (with the intrinsically high thermal conductivity) presented the improved heat transfer than alumina foams. In addition, electromagnetic induction heating was applied to regulate heat transfer in structured catalysts (e.g., Ni supported on carbon felt) for catalytic CO 2 methanation process, being able to improve heating/cooling rates with uniform heating environments and high energy efficiency 24‐28 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in situ infrared thermography was employed to examine the surface temperatures and development of hotspots due to the exothermicity of the reaction on structured catalysts based on different foams, showing that both SiC and aluminium foams (with the intrinsically high thermal conductivity) presented the improved heat transfer than alumina foams. In addition, electromagnetic induction heating was applied to regulate heat transfer in structured catalysts (e.g., Ni supported on carbon felt) for catalytic CO 2 methanation process, being able to improve heating/cooling rates with uniform heating environments and high energy efficiency 24‐28 …”
Section: Introductionmentioning
confidence: 99%
“…The same properties have even been reached with stainless steel electrodes, upon proper electrochemical activation [22,23]. The choice of FeNi3 comes from its good heating properties and activity for the Sabatier reaction [24]. In this study, the electrochemical activity of the materials has been measured with a RDE.…”
Section: Introductionmentioning
confidence: 66%
“…Ni peaks. A Mössbauer study was also undertaken to confirm the FeNi3 material, and will be further reported [24]. with the synthesis routes employed (2.8 at.% of Pt, which corresponds to ~ 0.01 wt.% of Pt, was used to start the nucleation for Ni NPs syntheses).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Here, all the phenomena of alloying, dealloying, and oxidation that we have highlighted in this Perspective can be present and can participate in the catalysis under the magnetic stimulus. [37][38][39][40][41][42]…”
Section: Magnetic Propertiesmentioning
confidence: 99%